If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19x + 6 = 44 Reorder the terms: 6 + 19x = 44 Solving 6 + 19x = 44 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 19x = 44 + -6 Combine like terms: 6 + -6 = 0 0 + 19x = 44 + -6 19x = 44 + -6 Combine like terms: 44 + -6 = 38 19x = 38 Divide each side by '19'. x = 2 Simplifying x = 2
| 24-5x=24-9x | | 4=-16t^2+45t+6 | | 3y=4t/y^2 | | 42=-16t^2+60t+6 | | 3y=(4t/y~2) | | 45=-16t^2+60+6 | | 4x^2+32x=-23 | | 35=-16t^2+60+6 | | 3(x-2)+5(x-2)=15x | | -9x+y=52 | | 42=-16t^2+60+6 | | 26-r=2r+2 | | (3x+1)+55=x | | 40=-16t^2+60+6 | | -2(13-m)=(m-19)-6 | | 12r+30-72=0 | | 100x+7x=111.28 | | 129+3x=x | | 40=-16t^2+46+6 | | 2r+26=r-2 | | 42=-16t^2+46+6 | | y=2(x-4)(x+2) | | (1+4x)+93=x | | 5xy+8=0 | | Y=-6+19 | | (5x+1)+51=x | | 26+r=2r-2 | | 5x-7=-202 | | 2r+26=4r-2 | | -8(r+9)-7=9 | | xe^(-t)*(dx)/(dt)=t | | 10=3x+-5 |